PENGARUH SISTEM PENILAIAN KINERJA PEGAWAI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PEGAWAI KANTOR PEMERINTAHAN KECAMATAN BARRU KABUPATEN BARRU - Kurnia Kurnia Kurnia; Muhammad Idris; Asri Asri (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine and analyze (1) the effect of the employee performance appraisal system and career development toward the employee job satisfaction at the Government Office in Barru Regency partially and simultaneously (2) the most dominant variable affects the employee performance at the Barru District Government Office in Barru Regency. This study used a survey method and Implemented at the Government Office in Barru Regency from November to December 2019. The population in this study were all employees at the Government Office in Barru Regency by 56 people. Sampling in this study used a saturated sampling technique (census) in which all the population in this study were sampled. The sample used in this study were 56 people. Data analysis used multiple regression analysis. The results show that (1) there is a positive and significant effect between the employee performance appraisal system and career development toward the job satisfaction partially and simultaneously on employee performance at the Government Office in Barru Regency (2) career development is the most dominant variable affects the employee performance at the Government Office in Barru Regency.